Composición del volcanismo cenozoico en los Andes Nordpatagónicos (43º-43º30’S, Chubut) - Fernández Paz, Lucía (2019)
Composition of Cenozoic volcanism in the North Patagonian Andes (43º-43º30-S, Chubut). Field, structural and geochemical analyses on the area between Trevelin and Tecka localities allow differentiating two volcanic units. A bimodal dacitic and basaltic volcanic sequence crops out to the north, assigned to the Pilcaniyeu Belt, based on stratigraphical relationships. This unit is geochemically characterized as transitional to arc. Toward the south, mainly andesitic volcanism shows a clearer arc signature, which correlates with El Maitén Belt volcanic arc setting.